2020
DOI: 10.5115/acb.18.169
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin supplementation shows modulatory influence on functional and morphological features of hippocampus in mice subjected to arsenic trioxide exposure

Abstract: Since, oxidative stress has been suggested as one of the mechanisms underlying arsenic-induced toxicity, the present study focused on the role of antioxidant (curcumin) supplementation on behavioral, biochemical, and morphological alterations with context to mice hippocampus (CA1) following arsenic trioxide (As 2 O 3 ) administration. Healthy male Swiss albino mice were divided into control and experimental groups. As 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In adult mice exposed to As chronically, morphological changes in the hippocampus such as the loss of the hippocampal packing arrangement of pyramidal neurons, an indistinct nucleolus, and neurons with pycnotic and fragmented nuclei were observed [188]. In the same study, a reduction in neuronal density and cell layer thickness was found after As 2 O 3 exposure [188]. In vitro evidence has also shown that arsenite reduced neurite production, outgrowth, and complexity in newly differentiating PC12 cells [220].…”
Section: Morphological Alterations Induced By As Exposurementioning
confidence: 73%
“…In adult mice exposed to As chronically, morphological changes in the hippocampus such as the loss of the hippocampal packing arrangement of pyramidal neurons, an indistinct nucleolus, and neurons with pycnotic and fragmented nuclei were observed [188]. In the same study, a reduction in neuronal density and cell layer thickness was found after As 2 O 3 exposure [188]. In vitro evidence has also shown that arsenite reduced neurite production, outgrowth, and complexity in newly differentiating PC12 cells [220].…”
Section: Morphological Alterations Induced By As Exposurementioning
confidence: 73%